PENDAMPINGAN SISWA OLEH KADER “GEMPI KESPRO” GENERASI MUDA PEDULI KESEHATAN REPRODUKSI DI SMPIT BINA INSANI KOTA KEDIRI - Erna Rahma Yani; Koekoeh Hardjito; Suwoyo Suwoyo (Jurnal Abdi Masyarakat, 2022)
Reproductive health issues are always an interesting topic of discussion among youth groups, including junior high school students. This community service activities aims to realize SMPIT Bina Insani Kediri as a school with a "gempi kespro" perspective, namely a school that has concern for reproductive health. Activities have started in 2021 with the formation of the Gempi Kespro Cadre and continued with training involving 35 students. This year (2022) is the 2nd year of implementing community service activities with the target of student mentoring activities by the Gempi Kespro Cadre to provide information and education on adolescent reproductive health issues under the supervision of the Gempi Kespro Advisor. Each cadre is given the opportunity to accompany 1 student by using the module, pocket book and Gempi Kespro comic, as a medium of information and education. From the activities carried out, it can be seen that there was an increase in participants' knowledge about adolescent reproductive health, including: reproductive organ anatomy, physiology, puberty and adolescent reproductive health problems. From the evaluation results, it was also found that 91.43% of cadres and 85.71% of participants stated that they were satisfied and benefited from participating in this activity. The majority of participants stated that the benefits obtained were in the form of: information about reproductive health (92.86%), the ability to communicate with friends (97.14%), having an interest in the world of health (74.29%). This activity is expected to be continued in the 3rd year with the target of strengthening school infrastructure with the concept of Gempi Kespro.Keywords: students, cadres, mentoring, reproductive health